Детское чтение: альманах ([главный редактор О. Н. Пилюгин]) - Пилюгин Олег Николаевич (2016)
Экземпляры: БС (20170123) / Инвентарный номер: РТШ54539 / Сис.шифр: Р2 / Авт.знак: Д 38 / ГРНТИ: 17.82.93 / ББК: 84(2)